United Arab Emirates : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper discusses performance and risks posed by government-related entities (GREs) in the United Arab Emirates (UAE). GREs continue to be a major source of growth and development for the UAE, but they also pose significant fiscal and financial risks. GREs' debt remains high in the UAE, although it is declining and remains actively managed. To mitigate GREs' risks, the authorities should build on recent progress and develop an integrated approach, including implementing prudent fiscal policies, enhancing macro- and microprudential frameworks, controlling GREs' borrowing and integrating them into the public debt management framework, and further strengthening corporate governance and transparency.